VISUALIZAÇÃO HIERARQUICA APLICADA À METANÁLISE DA EFICIÊNCIA DO FUNGICIDA FLUQUINCONAZOL EM SEMENTES DE SOJA PARA O CONTROLE DA FERRUGEM ASIÁTICA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
Asian soybean rust caused by Phakopsora pachyrhizi, is one of the main phytosanitary problems of soybean in Brazil. Aiming to reduce the losses caused by the pathogen, the treatment of soybean seeds with fungicide fluquinconazole has motivated researchers to conduct studies and simulate their performance. The compilation of these various studies may be conducted by the meta-analysis, which is a probabilistic technique that produces a result which summarizes studies. In agricultural context, meta-analysis is used to perform empirical estimates of technical efficiency for the development of productivity and economic research of agriculture, such as the use of the fungicide fluquinconazole. Meta-analysis can be applied through existing software such as R, run through commands, and WMA, which operates through a graphical user interface for data entry made by the user. The results generated by both software are shown in graphical form without providing interactivity with the user, neither reproducing a friendly software and easy to understand interface. This study applied meta-analysis using the WMA Software, which uses R to calculate the statistical results, to determine the efficiency of fungicide fluquinconazole in soybean seed, used to minimize the impact of the asian rust disease in the crop productivity. To provide a dynamic display of obtained results by meta-analysis, this study created a method to identify the best information visualization technique to represent hierarchical data. This method was applied to identify which better visualization technique represented the graphic forest plot, namely, bifocal tree. Changes were made at the WMA, such as: incorporation of a new effect measure, change in the help system and font files and the implementation bifocal tree technique using Gephi as a support tool. The implementation allowed to create a more interactive environment for analyzing the results of the R and provides two display options for the user: basic and advanced. The advantages of the visualization are that the user can explore more the data and results. In this study it was observed that when fluquinconazole was used to minimize the effects caused by rust soybean productivity (yield) was improved.
Keywords: ferrugem asiática da soja; metanálise; bifocal tree; ferramentas de metanálise; soybean rust; meta-analysis; bifocal tree; meta-analysis tools; CNPQ::CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO